2015
DOI: 10.2147/ceor.s78115
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating ulipristal acetate in the care of symptomatic uterine fibroids: a Canadian cost-utility analysis of pharmacotherapy management

Abstract: ObjectiveTo present a Canadian economic evaluation on the cost-utility of ulipristal acetate (5 mg orally daily) compared to leuprolide acetate (3.75 mg intramuscular monthly) in the treatment of moderate-to-severe symptoms of uterine fibroids in women eligible for surgery.MethodsA probabilistic decision tree was constructed to model the pre-operative pharmacological management of uterine fibroids under the primary perspective of the Ontario public payer. The model parameterized data from clinical trials, obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The most recent economic evaluation study in this field was a cost-utility analysis to assess ulipristal acetate for the care of symptomatic uterine fibroids in comparison with leuprolide, in Canada. In this study, the model suggested that ulipristal acetate strategy dominated leuprolide over the range of alternative settings as it is provided to Canadian patients, with more quality-adjusted life years (QALYs) at a lower cost from both a healthcare payer and a societal perspective 23 . As the use of ulipristal acetate has been authorized by the manufacturer worldwide, we can expect more research to firmly establish the contribution of ulipristal acetate in the management of uterine fibroids patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The most recent economic evaluation study in this field was a cost-utility analysis to assess ulipristal acetate for the care of symptomatic uterine fibroids in comparison with leuprolide, in Canada. In this study, the model suggested that ulipristal acetate strategy dominated leuprolide over the range of alternative settings as it is provided to Canadian patients, with more quality-adjusted life years (QALYs) at a lower cost from both a healthcare payer and a societal perspective 23 . As the use of ulipristal acetate has been authorized by the manufacturer worldwide, we can expect more research to firmly establish the contribution of ulipristal acetate in the management of uterine fibroids patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian economic study evaluated the cost utility of preoperative UPA administration relative to LA in women with moderate-to-severe symptoms of UFs. It showed an emphasizing domination of UPA strategy over LA, as it provided patients with more quality-adjusted life years (0.177 versus 0.165) at a lower cost ($1273 versus $1366) with fewer side effects and faster bleeding control [ 143 ]. A similar study was conducted in Mexico, concluding that UPA is a cost-effective alternative to surgery, as 21% of the patients treated with UPA avoided hysterectomy, which translates to $47,614,017 USD being saved for every 1000 patients.…”
Section: Treatment Options For Uterine Fibroidsmentioning
confidence: 99%
“…Their analysis concluded that UPA provided more quality-adjusted life years at a lower cost than leuprolide, because of its faster control of bleeding, lower incidence of hot flashes, and reduced healthcare resource consumption. 5 We agree that further robust analyses will occur only after long-term evaluation; currently, there are several long-term studies ongoing for the SPRM class of medications globally. Beyond clinical trials, a prospective observational noninterventional the Canadian women wiTh Uterine fibroids (UF) REgistry (CAPTURE) of 1500 women with symptomatic fibroid tumors has completed enrollment.…”
Section: Replymentioning
confidence: 75%